Nonlinear buckling behavior of hybrid composites with different notch types - Erdem, Serkan; Gur, Mustafa; Kaman, Mete Onur (Walter de Gruyter Gmbh, 2021)
In this study, the effect of change of notch type on non-linear buckling behavior in composite plates was investigated experimentally and numerically. The composite plate is produced by applying the vacuum infusion method using carbon and aramid hybrid woven fabric and epoxy. Primarily, in the composite plates, a circular hole in the middle, a U single edge notch and semicircle double edge notches are formed. The specimens were subjected to buckling tests, being placed on their two edges, while the others were free. Afterwards, the load displacement graphs of the plates under pressure load were obtained experimentally for the behavior before and after buckling. In the numerical study, non-linear buckling analysis was performed using the finite element method. As a result, experimental and numerical buckling behaviors were obtained in accordance with each other. Since the net cross section bearing the pressure load is equal for all notch types, an effective difference between the maximum damage loads has not been achieved. So, the variation of notch type does not change the load displacement behavior characteristics of the plates after buckling. However, due to the unsymmetrical geometry in U notched plates, an uneven change in horizontal displacements along the width of the plate was achieved. The maximum stress concentration formed around the notch increased after buckling with the increase of displacement in vertical direction.
Keywords: Hybrid composites; non-linear buckling; notch effect; finite element method